Entanglement witness measurement of time-bin two-qubit states using fiber-based Franson interferometers - Hwang, Kyumin; Seong, Jiheon; Park, Kyungdeuk; Kim, Jinwook; Pramanik, Tanumoy; Bae, Joonwoo; Shin, Heedeuk (Frontiers in Physics, 2023)
Entanglement, that is, quantum correlations that do not have a classical counterpart, is a precondition to establishing communication protocols beyond the existing classical ones, such as quantum key distribution that achieves a higher level of security without computational assumptions. In this work, we present a proof-of-demonstration of detecting various entangled states, prepared by time-bin encoding with photons that are natural resources for long-distance quantum communication. We generate a maximally entangled state in time-bin qubits and verify the state in two ways. We first consider measurements that realize entanglement witnesses for the verification of entanglement. We then perform a quantum state tomography for the full characterization. Experimental resources are also discussed.